2012
DOI: 10.1158/0008-5472.sabcs12-s1-7
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-7: Phase III trial evaluating the addition of bevacizumab to endocrine therapy as first-line treatment for advanced breast cancer – First efficacy results from the LEA study.

Abstract: Background: Preclinical data (de la Haba J, AACR 2011) and retrospective clinical data (Mander P, Cancer 2003; Linderhol B, JCO 2000) suggest that high vascular endothelial growth factor (VEGF) levels in breast tumors are associated with a decreased response to endocrine therapy. We designed the randomized phase III LEA study of first-line bevacizumab in combination with hormone therapy in endocrine responsive advanced breast cancer patients to address the hypothesis that anti-VEGF treatment can prevent resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Retrospective clinical data showed that decreasing VEGF level may restore sensitivity and improve efficacy to hormonal therapy (22). Phase III LEA study showed that there was a trend of longer progression-free survival in patients treated with bevacizumab and hormone therapy in HR-positive advanced breast cancer (23). Corroborating the data illustrated in Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Retrospective clinical data showed that decreasing VEGF level may restore sensitivity and improve efficacy to hormonal therapy (22). Phase III LEA study showed that there was a trend of longer progression-free survival in patients treated with bevacizumab and hormone therapy in HR-positive advanced breast cancer (23). Corroborating the data illustrated in Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Whether there is truly a benefit with bevacizumab for this subtype in the metastatic setting is currently being investigated (Table 1). Also, no additional value was found when bevacizumab was combined with either anti-HER2 or endocrine therapy in a subset of HER2 positive and ER positive MBC patients (Martin et al, 2012;Gianni et al, 2013). The negative BEATRICE, BETH and E5103 trials do not support a role for bevacizumab in the adjuvant treatment for TNBC, HER2 positive and HER2 negative patients (Miller et al, 2012;Cameron et al, 2013;Slamon et al, 2013).…”
Section: Vegf-a -Clinical Datamentioning
confidence: 97%
“…Three completed phase 3 studies-Letrozole/Fulvestrant and Avastin (LEA) [19,23], Phase 3 Study of Temsirolimus with Letrozole or Letrozole Alone (HORIZON) [20], and Breast Cancer Trials of Oral Everolimus-2 (BOLERO-2) [21,24]-have evaluated a targeted agent (the anti-vascular endothelial growth factor antibody bevacizumab in LEA; the mTOR inhibitors temsirolimus in HORIZON and everolimus in BOLERO-2) in combination with endocrine therapy in postmenopausal women with HR + advanced breast cancer. Patients enrolled in the LEA study received bevacizumab plus either letrozole or fulvestrant, or letrozole or fulvestrant alone, as first-line therapy for HR + advanced breast cancer (N = 374).…”
Section: Endocrine Therapy In Combination With Molecular-targeted Thementioning
confidence: 99%